2009
DOI: 10.1063/1.3180824
|View full text |Cite
|
Sign up to set email alerts
|

Two-dimensional (2+n) resonance enhanced multiphoton ionization of HCl: State interactions and photorupture channels via low-energy triplet Rydberg states

Abstract: Mass spectra were recorded for (2+n) resonance enhanced multiphoton ionization (REMPI) of HCl as a function of resonance excitation energy in the 81,710-82,870 cm(-1) region to obtain two-dimensional REMPI data. Small but significant fragmentations and H(+), Cl(+), as well as HCl(+) formations are found to occur after resonance excitations to the triplet Rydberg states f (3)Delta(2)(v(') = 0), f (3)Delta(1)(v(') = 0), and g (3)Sigma(+)(1)(v(') = 0). Whereas insignificant rotational line shifts could be observe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
56
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(59 citation statements)
references
References 32 publications
3
56
0
Order By: Relevance
“…Both groups investigated the ionization/fragmentation pathways through various vibrational bands of the B 1 Σ + (0 + ) state. Very recently, Kauczok et al [22] have reported similar studies on the singlet and triplet Δ states that previously were identified as being in resonance with selected rovibrational states of the B 1 Σ + (0 + ) state [16][17][18].…”
Section: Introductionmentioning
confidence: 74%
See 4 more Smart Citations
“…Both groups investigated the ionization/fragmentation pathways through various vibrational bands of the B 1 Σ + (0 + ) state. Very recently, Kauczok et al [22] have reported similar studies on the singlet and triplet Δ states that previously were identified as being in resonance with selected rovibrational states of the B 1 Σ + (0 + ) state [16][17][18].…”
Section: Introductionmentioning
confidence: 74%
“…The fragmentation ratio (Cl + /HCl + ) does not only show a smooth dependence on the excitation energy, but also crucially depends on the nature of the electronic states as well as on vibrational and rotational quantum numbers [16,18,20]. However, independently of the excitation energy, there exist bands which do not exhibit any significant fragmentation at all.…”
Section: To the Electronic Transitions B[v/e](mentioning
confidence: 99%
See 3 more Smart Citations